SPECIFIC-INDUSTRY ESG STANDARD ALIGNING: SASB STANDARD COMPLIANCE CASE STUDY OF PT BIO FARMA - Ghifari, Muhamad Haseemy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The study identifies critical gaps in Bio Farma's ESG reporting practices, particularly in the context of sustainability metrics under the Global Reporting Initiative (GRI) standards, which were deemed insufficient by stakeholders and regulatory audits. To address these challenges, this research proposes transitioning to the Sustainability Accounting Standards Board (SASB) Biotechnology & Pharmaceuticals standard to improve alignment with investor expectations and industry–specific benchmarks. The study employs a two-pronged methodology: gap analysis and benchmarking analysis. The gap analysis identifies unreported or insufficiently reported SASB metrics across environmental, social, and governance dimensions. Benchmarking analysis examines industry-leading companies’ ESG reporting practices to derive actionable solutions that align Bio Farma with investor expectations and industry-specific financial materiality. Findings highlight significant discrepancies in areas such as clinical trial safety, affordability and pricing transparency, product traceability, and counterfeit drug management. Best practices from leading global pharmaceutical firms suggest robust reporting frameworks, enhanced data transparency, and a focus on quantifiable performance metrics. Based on these insights, the thesis proposes solutions for Bio Farma to close the reporting gaps, optimize SASB-aligned disclosure, and improve their reputation and accountability among investors and stakeholders.